2010
DOI: 10.1080/00085030.2010.10768134
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Fire-Related Deaths in Alberta

Abstract: Burnt remains and fire-related research are growing areas of investigation in forensicanthropology;however,forthisresearchtobevaluabletocriminaldeath investigationsitmustbecomparablewithrealdeathcircumstances.Toensurethis relevance,anunderstandingofthecircumstances(andvictimprofiles)relatingto fatal fires is required. As a first step in addressing these issues, this paper examines and interprets fire deaths occurring in Alberta, Canada over a ten-year periodbetweenJanuary1999andDecember2008.Theresultsshowthat2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Alcohol consumption rates in the UK appear to be declining for younger and middle aged individuals, but appear to be increasing for older and more affluent individuals [3]. Both smoker's materials and alcohol consumption had been previously identified as fire risk factors [23], [41], and for the period 2006-2016 in Merseyside, 51% of fire fatalities involved smoker's materials, and 40% of fire fatalities involved alcohol consumption.…”
Section: Population Behaviours and Lifestyle Trends And Fire Riskmentioning
confidence: 99%
“…Alcohol consumption rates in the UK appear to be declining for younger and middle aged individuals, but appear to be increasing for older and more affluent individuals [3]. Both smoker's materials and alcohol consumption had been previously identified as fire risk factors [23], [41], and for the period 2006-2016 in Merseyside, 51% of fire fatalities involved smoker's materials, and 40% of fire fatalities involved alcohol consumption.…”
Section: Population Behaviours and Lifestyle Trends And Fire Riskmentioning
confidence: 99%
“…The other GIS maps included areas with a prevalence of 'harmful' or 'hazardous alcohol consumption and fire fatalities in accidental dwelling fires, areas with a prevalence of 'harmful' or 'hazardous alcohol consumption with smoking prevalence and fire injuries in accidental dwelling fires, and areas with a prevalence of 'harmful' or 'hazardous alcohol consumption with smoking prevalence and fire fatalities in accidental dwelling fires. The GIS maps that included smoking prevalence as well as 'harmful' or 'hazardous alcohol consumption were required since a number of previous studied had linked alcohol related fire risks with smoking (Leth et al, 1998;Waterhouse (2010);CFB, 2015;Ballard et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Leth et al (1998) undertook a study of fatalities in dwelling fires in the municipality of Copenhagen in Denmark that identified smoking combined with alcohol intoxication as significant factors associated with residential dwelling fire fatalities. Waterhouse (2010) found a strong correlation between fire deaths and smoking and /or alcohol consumption in a study of fire related deaths in Alberta, Canada. Jordan et al (1999) in a study of house fire fatalities in Eastern Scotland identified alcohol intoxication, and social deprivation as significant factors in residential dwelling fire incidents.…”
Section: Literature Reviewmentioning
confidence: 92%